Calculation of the Torsion Stiffness of Overrunning Clutch in Wave Power Generation Device - Guo Xiancheng; Su Yi; Wang Honglin; Yuan Bo (Jixie chuandong)
The the switch mechanism of roller overrunning clutch is introduced,with wave power generation device transmission system as example.A computational model based on elasticity mechanics is established and the physical properties are analyzed in the engagement process.The torsion stiffness expression of each component are deduced and torsion stiffness as a whole in series form is obtained finally.The calculation shows that overrunning clutch torsion stiffness is small compared to the other components.The results provide a theoretical basis for dynamics analysis,parameter optimize design and reliability study of overrunning clutch in wave power generation device transmission system.